The Contributions of Creativity to the Learning Process within Educational Approaches for Sustainable Development and/or Ecosocial Perspectives: A Systematic Review - Utdin Harvey López; Mercedes Vázquez-Vílchez; Purificación Salmerón-Vílchez (MDPI AG, 2024)
This systematic review identifies the contributions of creativity to learning and its integration into teaching within educational approaches with an ecosocial and/or sustainable perspective based on scientific publications in the Web of Science and SCOPUS databases, following the PRISMA methodology guidelines. This study establishes a comprehensive understanding of creativity from a sociocultural perspective and examines the relationship between creativity and educational approaches based on sustainable education. The results highlight that creativity is incorporated into teaching in a cross-cutting manner in the ideation, design, and implementation of pedagogical strategies that include diverse techniques, resources, and methodologies. Creativity contributes to learning by being multifaceted and transforming the student experience through the identification, understanding, appropriation, and applicability of concepts. Various strategies and methodologies are identified that promote creativity by involving students in collaborative and reflective processes. Creativity stimulates imagination, interdisciplinary and intercultural integration, and experimentation. The fundamental role of the teacher and the learning environment is emphasized. Finally, the need to integrate creativity into educational plans from these approaches is highlighted, fostering the adaptability to uncertainty and the generation of creative and sustainable responses. This review provides a synthesized and updated resource for teachers and individuals interested in the relationship between creativity, learning, and sustainability.